Plasticity of antimicrobial and phagocytic programs in human macrophages. Issue 2 (11th November 2018) - Montoya, Dennis; Mehta, Manali; Ferguson, Benjamin G.; Teles, Rosane M. B.; Krutzik, Stephan R.; Cruz, Daniel; Pellegrini, Matteo; Modlin, Robert L.
Summary: Macrophage (M Φ ) polarization is triggered during the innate immune response to defend against microbial pathogens, but can also contribute to disease pathogenesis. In a previous study, we found that interleukin‐15 (IL‐15) ‐derived classically activated macrophages (M1 M Φ ) have enhanced antimicrobial activity, whereas IL‐10‐derived alternatively activated macrophages (M2 M Φ ) were highly phagocytic but lacked antimicrobial activity. Given that the ability to modulate M Φ polarization from M2 M Φ to M1 M Φ may promote a more effective immune response to infection, we investigated the plasticity of these M Φ programs. Addition of IL‐10 to M1 M Φ induced M2‐like M Φ, but IL‐15 had little effect on M2 M Φ . We determined the set of immune receptors that are present on M2 M Φ, elucidating two candidates for inducing plasticity of M2 M Φ, Toll‐like receptor 1 (TLR1) and interferon γ (IFN‐ γ ) receptor 1. Stimulation of M2 M Φ with TLR2/1 ligand (TLR2/1L) or IFN‐ γ alone was not sufficient to alter M2 M Φ phenotype or function. However, co‐addition of TLR2/1L and IFN‐ γ re‐educated M2 M Φ towards the M1 M Φ phenotype, with a decrease in the phagocytosis of lipids and mycobacteria, as well as recovery of the vitamin‐D‐dependent antimicrobial pathway compared with M2 M Φ maintained in polarizing conditions. Similarly, treatment of M2 M Φ with both TLR2/1L and anti‐IL‐10 neutralizing antibodies led to polarization to the M1‐like M Φ phenotype and function. Together, our data demonstrate an approach to induce M Φ plasticity that provides the potential for re‐educating M Φ function in human mycobacterial disease to promote host defense and limit pathogenesis. Abstract : We investigate the mechanisms by which IL‐15 versus IL‐10 polarized M Φ are re‐educated in an effort to understand M Φ plasticity in diseases in which M Φ contribute to pathogenesis. We demonstrate that the re‐education of M2 M Φ into M1‐like M Φ by co‐addition of TLR2/1L and IFN‐ γ led to up‐regulation of key components of the vitamin D antimicrobial pathway and down‐regulation of phagocytic activity. Together, our data demonstrate an approach to induce MF plasticity that provides the potential for re‐educating MF function in human mycobacterial disease to promote host defense and limit pathogenesis.